Phase Transformation in Laser‐Induced Micro‐Explosion in Olivine (Fe, Mg)2SiO41. Issue 6 (31st March 2014) - Buividas, Ričardas; Gervinskas, Gediminas; Tadich, Anton; Cowie, Bruce C. C.; Mizeikis, Vygantas; Vailionis, Arturas; de Ligny, Dominique; Gamaly, Eugene G.; Rode, Andrei V.; Juodkazis, Saulius; Travitzky, Nahum; Medvedovski, Eugene
<x xml:space="preserve">Abstract</x> We show that micro‐explosions generated by tightly focused single pulses of a femtosecond laser in olivine have produced change of iron valence state. Chemical and structural changes were investigated using synchrotron X‐ray spectroscopy, and Raman scattering. Near edge X‐ray absorption fine structure (NEXAFS) spectra from laser‐affected zone of olivine crystal indicate a modified chemical bonding and a possible formation of regions containing a new crystalline phases of iron. Raman scattering from the laser‐affected zone regions reveals loss of crystalline order and formation of a mixture of nano‐crystallites due to melting and re‐solidification of olivine. These results indicate that spatial separation between ions of different mass occurs in hot, highly excited olivine. The present study confirms that this mechanism may present a general pathway toward creation of novel crystalline and amorphous nano‐materials using fs laser‐induced confined micro‐explosions.